Pengembangan Lembar Kerja Murid (LKM) untuk Melatih Keterampilan Argumentasi Murid pada Materi Laju Reaksi Kelas XI SMA - Sugiarti, Tutut; Yonata, Bertha (UNIB Press, 2025)
This study aimed to determine the feasibility of student’s worksheet (LKM) for training students' argumentation skills in reaction rate material. The feasibility of LKM was reviewed in terms of validity, practicality, and effectiveness. The type of research used was Research and Development (R&D) with a 4D development model by Thiagarajan with three stages, namely definition, design, and development. A limited trial was conducted in class XI-5 at SMAN 1 Singgahan Tuban. The analysis of the feasibility of the LKM from the validity aspect, as seen from the content and construct, yielded a mode score of 5 in the highly valid category. The practicality aspect of the LKM was seen from the percentage of student response questionnaires of 98.07% and student activity observation sheets of 95.67%, which were classified as highly practical. The effectiveness aspect was analyzed based on the increase in pretest and posttest scores for argumentation skills and learning outcomes, reviewed through a paired sample t-test analysis. Both had a P-Value (1-tailed) of 0.000, so the P-Value (1-tailed) < 0.005, leading to the rejection of H0 and acceptance of H1. Therefore, it can be concluded that LKM is suitable for use as a learning medium to train students' argumentation skills in reaction rate material.